Livoirit mouvemente : Jeunes, mdias et politique en Cte dIvoire - Bahi, Aghi (Book collections on Project MUSE., 2013)
The affirmation of cultural identity developed during the colonial and postcolonial years which has been the topic of bitter debates, is the root cause of the Ivorian crisis. However, is Ivoirity not a political maneuver or should it be viewed as the expression of liberal nationalism? This book traces the concept from its origins, explicates the conditions and context of the creation of a cultural nationalism which, progressively, has charted the course of an ethnic nationalism. The phenomenon of Ivoirity is inscribed in an already old historicity which feeds on cultural claims and affirmations. It seems to be a logical consequence of the policies of ivorisation of employment and capital initiated in the 1970s. There was a real consensus on the question of Ivoirity among the stake holders between 1960 and 2010. Their different managements of the citizenship questions and largely that of identity as well as the various "Trends" of Ivoirity are evidence. The narrative of Ivoirity is a response given by leaders who lack political imagination to resolve the political problems and challenges posed by multiform crises facing the country. As such, what could be the symbolic effects - the effectiveness and efficiency - of Ivoirity on the youths and the Media in a broader sense and even to Ivorian postcolonial politics in Côte d'Ivoire? This book also adopts a bottom-up approach with particular attention paid to the role of youths in media outlets, popular songs, street discussion forums created by youths (agoras, parliaments, and grins). The ties between youths and Ivoirity can be researched through such social phenomena. Through this, the book explores aspects of the Ivorian crises and inevitably, the 2010 Presidential elections and the stakes of the crises that followed.